2012
DOI: 10.1073/pnas.1202546109
|View full text |Cite
|
Sign up to set email alerts
|

The protein expression landscape of the Arabidopsis root

Abstract: Because proteins are the major functional components of cells, knowledge of their cellular localization is crucial to gaining an understanding of the biology of multicellular organisms. We have generated a protein expression map of the Arabidopsis root providing the identity and cell type-specific localization of nearly 2,000 proteins. Grouping proteins into functional categories revealed unique cellular functions and identified cell type-specific biomarkers. Cellular colocalization provided support for numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
166
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(172 citation statements)
references
References 85 publications
6
166
0
Order By: Relevance
“…Specifically, measures of mRNA correlate poorly with protein abundance, which is itself largely independent of phosphorylation status. The lack of correlation between mRNA and protein levels has been documented in other organisms (3)(4)(5)(6)(7)(8). However, we were surprised by the observation that many of the most abundant proteins had little to no measurable mRNA.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Specifically, measures of mRNA correlate poorly with protein abundance, which is itself largely independent of phosphorylation status. The lack of correlation between mRNA and protein levels has been documented in other organisms (3)(4)(5)(6)(7)(8). However, we were surprised by the observation that many of the most abundant proteins had little to no measurable mRNA.…”
Section: Discussionmentioning
confidence: 59%
“…Typically, measurements of mRNA abundance are used to infer the proteotype (1,2). However, it has become clear that mRNA levels are poorly correlated with protein abundance (3)(4)(5)(6)(7)(8). Proteomewide surveys are crucial for bridging this gap and defining specific cellular proteotypes.…”
mentioning
confidence: 99%
“…However, a growing body of research has found only moderate correlation between transcript and protein abundance (Gygi et al, 1999;Schwanhäusser et al, 2011;Petricka et al, 2012;Vogel and Marcotte 2012;Walley et al, 2013;Ponnala et al, 2014). In this study, Pearson and Spearman rank correlation coefficients revealed moderate positive relationships between transcript and protein abundance in primary root tissues (Table II).…”
Section: Discussionmentioning
confidence: 72%
“…The data were derived from four individual microarray and proteomic studies in distinctive cell populations of the root (Birnbaum et al, 2003;Brady et al, 2007;Dinneny et al, 2008;Petricka et al, 2012). To compare the cellspecific gene expression of CK-related genes with the CK gradient maps ( Figure 5; Supplemental Figure 6), the data were classified into four categories corresponding to the cell-type populations in which M0028:GFP, J2812:GFP, pWOL:GFP, and pSCR:GFP are expressed.…”
Section: Discussionmentioning
confidence: 99%